2000
DOI: 10.1002/(sici)1096-9861(20000131)417:1<73::aid-cne6>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Does the visual system of the flying fox resemble that of primates? The distribution of calcium-binding proteins in the primary visual pathway ofPteropus poliocephalus

Abstract: It has been proposed that flying foxes and echolocating bats evolved independently from early mammalian ancestors in such a way that flying foxes form one of the suborders most closely related to primates. A major piece of evidence offered in support of a flying fox-primate link is the highly developed visual system of flying foxes, which is theorized to be primate-like in several different ways. Because the calcium-binding proteins parvalbumin (PV) and calbindin (CB) show distinct and consistent distributions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 58 publications
(112 reference statements)
2
7
0
Order By: Relevance
“…The morphological classes of interneurons defined by their expression of calcium-binding proteins and NPY in our study of atlantogenatans closely resembled the major types that have been described extensively in other eutherian mammals Ferrer 1994, 1995;Clemo et al 2003;Desgent et al 2005;Gao et al 2000;Glezer et al 1992Glezer et al , 1993Glezer et al , 1998Gonchar and Burkhalter 1997;Hof et al 1996aHof et al , 1999Hogan and Berman 1994;Ichida et al 2000;Lund and Lewis 1993;Nimchinsky et al 1997;Park et al 2000;Van Brederode et al 1990, as well as marsupials , and the monotreme echidna (Hassiotis et al 2005). This suggests that the common ancestor of all mammals possessed many of the same interneuron types expressing similar neurochemical profiles and that these cell classes were retained in all descendants.…”
Section: Morphology and Distribution Of Interneuronssupporting
confidence: 78%
“…The morphological classes of interneurons defined by their expression of calcium-binding proteins and NPY in our study of atlantogenatans closely resembled the major types that have been described extensively in other eutherian mammals Ferrer 1994, 1995;Clemo et al 2003;Desgent et al 2005;Gao et al 2000;Glezer et al 1992Glezer et al , 1993Glezer et al , 1998Gonchar and Burkhalter 1997;Hof et al 1996aHof et al , 1999Hogan and Berman 1994;Ichida et al 2000;Lund and Lewis 1993;Nimchinsky et al 1997;Park et al 2000;Van Brederode et al 1990, as well as marsupials , and the monotreme echidna (Hassiotis et al 2005). This suggests that the common ancestor of all mammals possessed many of the same interneuron types expressing similar neurochemical profiles and that these cell classes were retained in all descendants.…”
Section: Morphology and Distribution Of Interneuronssupporting
confidence: 78%
“…Larger (mean area = 149.1 μm 2 ) cells were observed in the dLGN compared to those in the SC and PNT of A. planirostris . A previous study in the gray-headed flying fox ( Pteropus poliocephalus ) revealed small neurons (106 μm 2 ) in the dLGN (Ichida et al, 2000 ) compared to those in the dLGN in A. planirostris . Scalia et al ( 2015 ) have performed an extensive study of subcortical visual centers in the bat Carolia perspicilata .…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies in bat, using fiber degeneration after eye removal or an intraocular CTb injection have shown lateral and medial layers in the dLGN, even though no quantitative approach has been performed (Cotter and Pierson Pentney, 1979 ; Cotter, 1985 ; Covey et al, 1987 ). In addition, three layers were identified in Pteropus poliocephalus (Ichida et al, 2000 ; Manger and Rosa, 2005 ) and six layers are classically described in primates (Fitzpatrick et al, 1980 ; Callaway, 2005 ). Taken together, these findings suggest that the visual system in bats, including A. planrostris , might function as a series of parallel pathways, conveying different aspects of the visual information, similar to that seen in upper vertebrates, which to a great extent orient their behavior by sight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GluR1-immunoreactive (IR) neurons in the visual cortex of the monkey [3] and rat [15] have been described. Calcium-binding proteins are localized in the visual cortex of several mammalsvincluding human [2, 11, 20, 3336], monkey [2, 8, 12, 14, 19, 20, 40, 59, 60], dolphin [11, 12], cat [9, 21, 24, 54], rabbit [45], flying fox [23], ferret [10], rat [5, 13, 37], mouse [46], and hamster [31]. …”
Section: Introductionmentioning
confidence: 99%